Hazardous alcohol use, antiretroviral therapy receipt, and viral suppression in people living with HIV who inject drugs in the United States, India, Russia, and Vietnam. (1st December 2020) - Wagman, Jennifer A.; Wynn, Adriane; Matsuzaki, Mika; Gnatienko, Natalia; Metsch, Lisa R.; del Rio, Carlos; Feaster, Daniel J.; Nance, Robin M.; Whitney, Bridget M.; Delaney, Joseph A.C.; Kahana, Shoshana Y.; Crane, Heidi M.; et al.
Abstract : Objectives: In high-income countries, hazardous alcohol use is associated with reduced receipt of antiretroviral therapy (ART) and viral suppression among people living with HIV (PLHIV) who inject drugs. These associations are less understood in lower middle-income countries (LMIC) and upper middle-income countries. Design: We examined associations between hazardous alcohol use, ART receipt, and viral suppression among PLHIV who reported current or former injection drug use. Participants were from nine studies in the United States (high-income country), India (LMIC), Russia (upper middle-income country), and Vietnam (LMIC). Methods: Hazardous alcohol use was measured via Alcohol Use Disorders Identification Test. Outcomes were HIV viral suppression (viral load of <1000 RNA copies/ml) and self-reported ART receipt. Logistic regression assessed associations between hazardous alcohol use and both outcome variables, controlling for age and sex, among participants with current and former injection drug use. Results: Among 2790 participants, 16% were women, mean age was 37.1 ± 9.5 years. Mean Alcohol Use Disorders Identification Test scores were 4.6 ± 8.1 (women) and 6.2 ± 8.3 (men); 42% reported ART receipt; 40% had viral suppression. Hazardous alcohol use was significantly associated with reduced ART receipt in India (adjusted odds ratio = 0.59, 95% confidence interval: 0.45–0.77, P  < 0.001); and lower rates of viral suppression in Vietnam (adjusted odds ratio = 0.51, 95% confidence interval: 0.31–0.82, P  = 0.006). Conclusion: Associations between hazardous alcohol use, ART receipt, and viral suppression varied across settings and were strongest in LMICs. Addressing hazardous alcohol use holds promise for improving HIV continuum of care outcomes among PLHIV who inject drugs. Specific impact and intervention needs may differ by setting.